2021
DOI: 10.1155/2021/6616645
|View full text |Cite
|
Sign up to set email alerts
|

A New Experimental Approach for Hydraulic Fracturing Fluid Damage of Ultradeep Tight Gas Formation

Abstract: The unconventional resources from an ultradeep tight gas reservoir have received significant attention in recent decades. Hydraulic fracturing is the main method for tight gas reservoir development because of its extremely low permeability and porosity. During hydraulic fracturing, high hydraulic fracturing fluid (HFF) that invaded the zone near the fracture face may reduce gas relative permeability significantly and impede gas production. The sources of this damage can be the high capillary pressure (HCP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In order to effectively diagnose the predominant mechanism of face damage in fractures in tight sands, Li et al [109] proposed a new experimental method. In their work, two mechanisms are suggested as mostly being responsible for fracture face damage; high capillary pressure and swelling of water sensitive clays.…”
Section: Fracture Face Damagementioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively diagnose the predominant mechanism of face damage in fractures in tight sands, Li et al [109] proposed a new experimental method. In their work, two mechanisms are suggested as mostly being responsible for fracture face damage; high capillary pressure and swelling of water sensitive clays.…”
Section: Fracture Face Damagementioning
confidence: 99%
“…In their work, two mechanisms are suggested as mostly being responsible for fracture face damage; high capillary pressure and swelling of water sensitive clays. Li et al [109] integrated pressure transmission and pressure decay methods to determine the predominant cause of fracture face damage. They concluded that their method is able to distinguish the cause of the key mechanism in fracture face damage.…”
Section: Fracture Face Damagementioning
confidence: 99%
“…At times, the fracture propagation pressure is considered as the bottomhole treating pressure. In this case, its magnitude depends on the in situ stresses and the net drop in pressures [109]. The net pressure drop is influenced by the tortuosity between the wellbore and the fracture, and the viscous flows within the wellbore perforation tunnel and the propagating fracture.…”
Section: Fracturing Fluids and Fluid Systemsmentioning
confidence: 99%
“…These experiments allow for the quantification of the extent and direction of reservoir damage due to sensitivity. To gain further insight into the damage mechanisms, various core analysis tools such as cast thin section observation, XRD diffraction analysis, scanning electron microscopy, and micro and nano CT techniques are employed. Numerous researchers have investigated formation sensitivity using conventional core flow experiments in combination with microcore analysis techniques like CT and nuclear magnetic resonance (NMR). One study utilized X-ray microcomputed tomography (CT) analysis to evaluate formation damage in sandstone reservoirs, providing conclusive evidence of damage caused by clay swelling and fine migration during workover fluid and formation fluid flooding .…”
Section: Introductionmentioning
confidence: 99%